An act of transgression: performing arts as a subject choice within a coastal area of deprivation. Issue 3 (1st September 2020) - Colman, Aly; Colman, Geoffrey
ABSTRACT: This paper examines the perceptions and aspirations of secondary school pupils interested in a career in the performing arts. The pupils in this case study were participating in drama-based courses and this research offers findings relevant for those working in schools, FE and HE, as well as the creative arts industries. This research is located within a coastal area of deprivation, Waveside, situated within England, UK. We have used fictional names for the towns, school and participants in this research, to offer anonymity. England's coastal areas are often linked to deprivation. Within this context, a focus group of GCSE, A level and BTEC Drama pupils from Seagreen Secondary Academy, a secondary school in Waveside, provides the data that informs this research, with additional contextual narrative from the pupils' teacher. The findings show that to study a performing arts subject is perceived by some pupils as an act of transgression. These pupils resisted neoliberal curriculum priorities resulting in tensions between school, parents and friends. Those acting as gate-keepers to professional actor training and other career opportunities within the arts, may need to review practices for recruitment and development support within marginalised communities.